5x+3(2x-4)=43

Simple and best practice solution for 5x+3(2x-4)=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+3(2x-4)=43 equation:


Simplifying
5x + 3(2x + -4) = 43

Reorder the terms:
5x + 3(-4 + 2x) = 43
5x + (-4 * 3 + 2x * 3) = 43
5x + (-12 + 6x) = 43

Reorder the terms:
-12 + 5x + 6x = 43

Combine like terms: 5x + 6x = 11x
-12 + 11x = 43

Solving
-12 + 11x = 43

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 11x = 43 + 12

Combine like terms: -12 + 12 = 0
0 + 11x = 43 + 12
11x = 43 + 12

Combine like terms: 43 + 12 = 55
11x = 55

Divide each side by '11'.
x = 5

Simplifying
x = 5

See similar equations:

| 3v^2-2v-4=0 | | 2.5y+5= | | 9y-8y+3y= | | 18-(2x+8)=14 | | n-3n=13-4n | | -4y=-4x+10 | | n+5/7=2/3 | | 3x=y+11 | | 3.5+10m=7.98 | | 7r^2+6r+1=0 | | x+7/7=8/4 | | 16-9g=70 | | y=4-38-1.3 | | X+-z=yforz | | 3.5y+8= | | -4+x=3x+8 | | 2y=x-5 | | r^2-9r-12=0 | | -86-12=14a | | 5x-15+6=5x-9 | | 6.5x+3= | | -8x+5=37 | | 8(x+7)+5=8x+7 | | -10v=-5 | | k^2+9=38 | | -4d+6=16-9d | | 24+6x=9x | | 30=60l+20 | | 3v^2=-27v | | -1/2+-1+2/3= | | 2x+1.5=7.7 | | 9x-3-7x+4= |

Equations solver categories